2014
DOI: 10.1128/jvi.01259-14
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Upregulates Expression of the Lectin Galectin 9 via Induction of Beta Interferon

Abstract: Regulation of the lectin galectin 9 (Gal-9) was investigated for the first time during human cytomegalovirus (HCMV) infection. Gal-9 transcription was significantly upregulated in transplant recipients with reactivated HCMV in vivo. In vitro, Gal-9 was potently upregulated by HCMV independently of viral gene expression, with interferon beta (IFN-␤) identified as the mediator of this effect. This study defines an immunoregulatory protein potently increased by HCMV infection and a novel mechanism to control Gal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Although Galectin‐9 appears to be constitutively expressed in several organs including the spleen, it is possible that the levels of Galectin‐9 expressed in naive mice are not sufficient to induce apoptosis through Tim‐3. Studies by others have shown that Galectin‐9 expression is up‐regulated by inflammatory cytokines or viral infections . Therefore, we also tested whether Tim‐3 + Th1 cells were prone toward apoptosis in the context of acute LCMV infection, which induces a robust inflammatory response.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although Galectin‐9 appears to be constitutively expressed in several organs including the spleen, it is possible that the levels of Galectin‐9 expressed in naive mice are not sufficient to induce apoptosis through Tim‐3. Studies by others have shown that Galectin‐9 expression is up‐regulated by inflammatory cytokines or viral infections . Therefore, we also tested whether Tim‐3 + Th1 cells were prone toward apoptosis in the context of acute LCMV infection, which induces a robust inflammatory response.…”
Section: Discussionmentioning
confidence: 98%
“…Studies by others have shown that Galectin-9 expression is up-regulated by inflammatory cytokines or viral infections. [66][67][68][69][70][71][72][73][74] Therefore, we also tested whether Tim-3 + Th1 cells were prone toward apoptosis in the context of acute LCMV infection, which induces a robust inflammatory response. Again, we found no evidence for Tim-3 + Th1 cells being more sensitive to apoptosis compared with Tim-3 À cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To interrogate the IFN-independent, IRF3-dependent response to HCMV HFs have been engineered (92,93) to lack either IRF3 through expression of the nPro protein of bovine viral diarrhea virus (BVDV) (nPro/HFs) which binds and degrades IRF3 (94) or STAT1, by expression of the parainfluenza virus type 5 (PIV-5) V protein (V/HFs) which targets STAT1 for proteasomal degradation (95). These nPro/HFs and V/HFs were recently utilized, alongside IRF3 KO CRISPR/Cas9 HFs, to demonstrate that expression of viperin, ISG15, IFIT1, IFIT2, IFIT3, Mx1, and Mx2 mRNA during infection with HCMV can be induced in an IRF3-dependent, STAT1-independent manner (96).…”
Section: Figure 1 | Induction and Subversion Of The Innate Ifn Responmentioning
confidence: 99%
“…In addition, V/HF did not respond to IFNs even when stimulated with 1,000 pg/ml of IFN-␤ as determined by monitoring the relative mRNA levels of the ISGs protein kinase R (PKR) and ISG15 by quantitative reverse transcription-PCR (qRT-PCR) ( Fig. 1B and C) using a published protocol (32). The sequences of the primers used are indicated: GAPDH-F, 5=-TGTTCGTCATGGGT GTGAAC-3=; GAPDH-R, 5=-GGTGCTAAGCAGTTGGTGGT-3=; PKR-F, 5=-GCTGAGCACAGGGCTAGAAG-3=; PKR-R, 5=-A ACACCCTGGCATATAGTTGGA-3=; ISG15-F, 5=-GCGAACTC ATCTTTGCCAGTA-3=; ISG15-R, 5=-AGCATCTTCACCGTCA GGTC-3=.…”
mentioning
confidence: 99%